Nickel hydroxide nanosheet interacts with nitric oxide to stimulate glycolytic pathway, nutrient assimilation and defense system against arsenic toxicity in wheat - Sarika Kumari; Pravneet Kaur; Iram Wahid; Rafiq Ahmad; Byeong-Il Lee; Moksh Mahajan; M. Iqbal R. Khan (Plant Stress)
Arsenic (As) stress has been steadily causing large-scale loss in crop production. However, the advent of robust approaches to create nanoscale materials, such as nanosheets (NS), embodies a significant stepping milestone. The interaction between nickel hydroxide NS and plant signaling molecules, including nitric oxide (NO), has not been yet elucidated in mediating As stress tolerance in plants. The present study has reported the use of nickel hydroxide NS, wherein its application with NO has significantly impeded oxidative stress by regulating defense pathways and NO synthesis in the As-stressed wheat plants. Additionally, photosynthesis, glycolysis and source-sink responses were positively regulated by nickel hydroxide NS and NO upon As exposure, along with mineral nutrients enrichment. However, nickel hydroxide NS displayed better efficacy with NO in conferring As stress tolerance, which benefited wheat growth and yield output. Moreover, nickel hydroxide NS was effective in eliciting NO biosynthesis under As stress to sustain plant tolerance, even in the presence of NO scavenger. Conclusively, this study aims to enhance As stress tolerance in wheat by incorporating nickel hydroxide NS and exploring their interaction with NO to improve plant sustainability. The path to a greater sustainable future could be facilitated by this research in the area of nanobiotechnology-based agricultural implications.